Digital integrated circuits : analysis and design. - Ayers, John E., ....- (Boca Raton : CRC, 2004)
Samenvatting:" Stresses computer tools throughout--nearly every chapter includesSPICE examples and exercises" Includes laboratory exercises in most chapters, serving modern coursesthat integrate lecture and laboratory components" Presents bipolar as well as MOS concepts" Incorporates more than 100 solved examples that reinforce theconcepts, illustrate numerical quantities, and show the relativeimportance of different effects" Provides a Quick Reference table in each chapter that presents theimportant concepts, equations, design rules, and diagrams" Summarizes the basic properties and physics of semiconductors, diodes,bipolar transistors, and field-effect transistors in review chapters" Contains Web references that include sources of data sheets, SPICEmodels, and application notes" Prepares students for courses in VLSI design and VLSI fabricationWithqualifying course adoptions, you'll also get a complete Solutions Manual,and an Instructors Manual with lecture transparencies. The InstructorsManual
Contains PowerPoint slides along with equations, derivations, andsolved problems that you can write out during your presentations.There is no field of enterprise today more dynamic or more challengingthan Digital Integrated Circuits. But because of its rapid development,the field has quickly outgrown most of the standard textbooks. The fieldis also decidedly interdisciplinary. Engineers now must understandmaterials, physics, devices, processing electromagnetics, computer tools,and economics along with circuits and design rules, but few if any textstake the interdisciplinary approach that best prepares students for theirfuture studies and practice.Author John Ayers designed Digital Integrated Circuits: Analysis andDesign to meet three primary objectives: Take an interdisciplinary approach that will stay relevant for years tocome Provide broad coverage of the field relevant to students interested indesigning integrated circuits and to those aiming towards designing withintegrated circuits Focus on
The underlying principles rather than the details of currenttechnologies that will soon be obsoleteRich with pedagogical features and supplementary materials, this bookappears destined to set a new standard for digital integrated circuitstexts. It provides all of the materials you need to offer the bestpossible course for engineering or computer science students, and it'sclear, systematic presentation and wealth of solved examples build thesolid, practical foundation today's students need.Prerequisites: Students will need an upper-level undergraduateengineering and science background with courses in circuits, electronics,and digital logic.
Keywords: Digitale schakelingen; Schakeltechnieken